Penguatan Watak Kewarganegaraan Melalui Program Sabtu Budaya (Studi Kasus di Sekolah Menengah Atas Negeri 1 Lingsar) - Novianti, Delsy; Mustari, Mohamad; Sawaludin, Sawaludin (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
This study investigates the implementation and impact of the Cultural Saturday Program (Sabtu Budaya) as a culture-based co-curricular initiative at SMAN 1 Lingsar. Employing a qualitative descriptive case study design, data were gathered through observation, interviews, and documentation. The analysis focuses on the program's execution process and stakeholder perceptions, viewed through the theoretical framework of civic disposition. Findings reveal that the program comprises five core activities: Gema Gatra exercises, traditional music performances, traditional dances, traditional games, and art exhibitions. Results indicate highly positive perceptions from both students and teachers, who advocate for the program's continuation and expansion to ensure sustainable benefits. Furthermore, the study identifies that the program effectively strengthens essential civic dispositions, specifically compassion, compromise, self-discipline, patience, persistence, individual responsibility, and open-mindedness. These results underscore the significance of integrating cultural practices into the school environment to foster robust civic character among students.